Total extraperitoneal access for parietal peritonectomy for peritoneal surface malignancy: The 'cocoon' technique. (August 2020) - Kyriazanos, Ioannis; Papageorgiou, Dimitrios; Zoulamoglou, Menelaos; Marougkas, Meletios; Stamos, Nikolaos; Ivros, Nikolaos; Kalles, Vasileios
Abstract: Objective: Complete surgical cytoreduction is the most important prognostic factor of survival in patients with peritoneal metastases from various cancers, including ovarian cancer. In order to achieve the optimum result, surgeons use extensive procedures that involve peritonectomies and multivisceral resections. Cytoreductive surgery (CRS) aims to eliminate all macroscopic disease by achieving complete cytoreduction. This article describes a surgical approach designed to achieve total extraperitoneal access for parietal peritonectomy. Study design: Visceral resections and parietal peritonectomy procedures must be conducted for complete removal of all visible malignancy. This article presents a technique that combines existing surgical approaches (anterolateral parietal peritonectomy, complete pelvic peritonectomy with sleeve resection of the sigmoid colon, and right and left upper quadrant peritonectomies) to achieve access to the upper abdomen, the lateral abdomen and the pelvis while keeping the peritoneum intact. Results and conclusion: This approach facilitates the peritonectomies necessary for complete cytoreduction, and improves access to difficult sites such as the pelvis and the subdiaphragmatic areas in a standardized manner that can be reproduced safely by an experienced surgical team.